2015
DOI: 10.1038/jhg.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of rare/low-frequency variants of the mitochondria respiratory chain-related proteins in rheumatoid arthritis patients

Abstract: Exome sequencings were conducted using 59 patients having rheumatoid arthritis (RA) and 93 controls. After stepwise filtering, 107 genes showed less than 0.05 of P-values by gene-burden tests. Among 107 genes, NDUFA7 which is a subunit of the complex I in the mitochondrial respiratory chain was selected for further analysis based on previous reports. A case-control study was performed on the three single-nucleotide variants (SNVs) of NDUFA7 with 432 cases and 432 controls. An association was observed between N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…TYK2 is a member of the JAK family of proteins, which also includes JAK1, JAK2 and JAK3. A previous study has indicated that three common variants, I684S, A928A and P1104A, in TYK2 are protective in the pathogenesis of RA,36 40 but the accumulation of rare missense variants in TYK2 has not been significant 24–26 40. Our results showed that rare coding variants in TYK2 protected against the onset of RA in the Japanese population.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…TYK2 is a member of the JAK family of proteins, which also includes JAK1, JAK2 and JAK3. A previous study has indicated that three common variants, I684S, A928A and P1104A, in TYK2 are protective in the pathogenesis of RA,36 40 but the accumulation of rare missense variants in TYK2 has not been significant 24–26 40. Our results showed that rare coding variants in TYK2 protected against the onset of RA in the Japanese population.…”
Section: Discussionsupporting
confidence: 48%
“…This strategy worked well to pinpoint likely causal genes in other diseases, for example, IFIH1 in type 1 diabetes,18 interleukin (IL)-23 receptor in inflammatory bowel disease,19 MTNR1B in type 2 diabetes,20 PLD3 in Alzheimer’s disease,21 CARD9 and RNF186 in ulcerative colitis,22 and multigenic modules in Crohn’s disease 23. Several studies have applied this strategy to RA and have reported associations between RA and IL2R ,24 VSTM1 25 and the mitochondrial respiratory chain pathway 26. To identify rare variants in genes with relevant biological functions,24 25 large sample sizes are required to detect their signals.…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance between ROS production and elimination is thought to lead to the oxidative stress in RA patients which contributes to tissue damage and further to the chronicity of the disease [ 26 ]. Oxidative stress has therefore been considered to be involved in the onset of RA [ 15 , 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mitsunaga et al found a significant association between severe erosive RA and mitochondrial respiratory complex-related genes, that were major site of ROS generation [ 15 ]. They suggested that ROS were involved in cartilage and bone destruction through activation of osteoclast and fibroblast-like synoviocytes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation